Implementasi Model Penilaian Portofolio Dalam Pembelajaran Matematika Berbasis Lesson Study di SMP Muhammadiyah 1 Kartasura - Maudyla, Clara Virgia, Dr. Sumardi, M.Si (2016)
The purpose of this study to determine: (1) teachers understanding of SMP Muhammadiyah 1 Kartasura the portfolio assessment, (2) the implementation process model of portfolio assessment in mathematics-based lesson study, (3) an obstacle to implementation of the portfolio valuation models based math learning lesson. Descriptive qualitative research was conducted at SMP Muhammadiyah 1 Kartasura with the subjects in this study were students of class VII D totaling 36 students. Data collection techniques used include interviews, testing, evaluation and documentation. Data analysis techniques used in the study of data reduction, data presentation and conclusion. The results showed: (1) teacher at SMP Muhammadiyah 1 Kartasura yet clearly understand the portfolio assessment. (2) The implementation process of the model portfolio assessment in mathematics-based lesson study has been done has improved the value of the average math scores of students and has increased a better attitude over time (3) Obstacles encountered, students are less enthusiastic in participating in the learning process in class, classroom atmosphere less conducive, and the time for preparation is less efficient portfolio assessment.